2008
DOI: 10.1111/j.1365-2486.2008.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

GLOBE students, teachers, and scientists demonstrate variable differences between urban and rural leaf phenology

Abstract: The urban heat island effect, classically associated with high impervious surface area (ISA), low vegetation fractional cover (Fr), and high land surface temperature (LST), has been linked to changing patterns of vegetation phenology, especially spring growth. In this study, a collaboration with the Global Learning and Observations to Benefit the Environment (GLOBE) program, we investigated the effect of the urban environment on the timing of leaf budburst of native deciduous trees in seven cities: Asia (Tokyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 60 publications
1
37
0
2
Order By: Relevance
“…The influence of humidity on the other phases and species, however, was not that marked. The only other study comparing urban and rural phenology of tropical tree species also identified the potential importance of humidity (Gazal et al, 2008). Leafing phenology of tropical trees under a seasonal climate is driven mostly by precipitation and also by non-climatic parameters such as leaf longevity, water stress and increasing day length (Morellato et al, 2000;Borchert et al, 2005;Staggemeier and Morellato, 2011).…”
Section: Air Temperature Humidity and The Phenology Of Trees In Urbamentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of humidity on the other phases and species, however, was not that marked. The only other study comparing urban and rural phenology of tropical tree species also identified the potential importance of humidity (Gazal et al, 2008). Leafing phenology of tropical trees under a seasonal climate is driven mostly by precipitation and also by non-climatic parameters such as leaf longevity, water stress and increasing day length (Morellato et al, 2000;Borchert et al, 2005;Staggemeier and Morellato, 2011).…”
Section: Air Temperature Humidity and The Phenology Of Trees In Urbamentioning
confidence: 99%
“…We only found significant UHI-related differences for Tipuana in Campinas, whereas almost all phenophases of Tabebuia and all of Caesalpinia had small positive urban-rural differences (albeit not significant) that indicated an earlier onset in the countryside. Gazal et al (2008) reported earlier bud burst dates only in the tropical city of Bangkok (−23 d), but not in Korat (+9 d) or Dakar (+9 d). In addition, bud burst was delayed with increasing land surface temperature, suggesting a low temperature sensitivity, or other influencing environmental variables (e.g.…”
Section: Urban-rural Differences In Phenologymentioning
confidence: 99%
See 2 more Smart Citations
“…elevated CO 2 and N deposition) can also influence phenology (Cleland et al 2006). The recent establishment of the USA National Phenology Network (USA-NPN; https://www.usanpn.org/), 'citizen science' efforts such as ProjectBudBurst ( http://budburst.org/), and the GLOBE phenology project (Gazal et al 2008) all suggest a need for better documentation of biological responses to a changing world and highlight the importance of phenological monitoring to achieve this goal (Morisette et al 2009). …”
Section: Introductionmentioning
confidence: 99%